Pleurisia na suinocultura brasileira: avaliação da prevalência no pais e estudo da Pasteurella multocida como agente causador - Nascimento, Enio Rivelino Maria (2016)
Pleurisy is a chronic injury, originated from an inflammation of the parietal and visceral pleura, being important in pig farming due to the loss of performance of animals and carcasses in slaughterhouses. Pasteurella multocida, Haemophilus parasuis Actinobacillus pleuropneumoniae, Streptococcus suis and Bordetella bronchiseptica are the most important causative agents. To evaluate the incidence of stage and to study the prevalence in Brazil is important because from these studies can be formulated control programs vaccine and drug more appropriately, reducing costs and condemnations at slaughter. The identification of the causative agents of pleurisies, and the prevalence by phase and region of the country, besides the evaluation of the differences between P. multocida strains were the objectives of this work. Was used the P. multocida due to the prevalence and because lesions persist until slaughter resulting in greater economic losses. First, 420 exams with pleurisy in pigs were classified in a microbiology laboratory between 2013 and 2014, with 55% of HPS, 31% of P. multocida, 7% APP 7 %; 6% S. suis and 1% BB. Regarding age, it was observed that the prevalence of HPS was in the nursery phase between 30 to 70 days, the P. multocida was in the growth phase of 80 to 120 days, while the APP was the most frequent agent in termination from 130 to 180 days. The S.suis BB and presented with low series. HPS is more evident in the southern of Brazil, where prevails lower temperatures. In warmer climates, a similarity between the isolates of P. multocida and HPS was observed. Among the isolates of P.multocida, 36 samples in random order were selected, 6 per state in the country. DNA extraction was performed with subsequent reaction of PCR to verify the diversity among the samples. Of selected samples of P. multocida A and P. multocida D to SC and the Midwest (MS, MT and GO) we find similarity between the band patterns indicating proximity between samples, but to the selected MG, RS, PR and Southeastern states (SP and ES) observed a diversity in the number and distribution of bands with different migration suggesting a marked diversity, there are different patterns of strains of P. multocida in Brazil, suggesting the need for a specific protection for farm or cross-protection conferring a homologous protective immunity against all serotypes of P. multocida. Regarding antibiograma, there was considerable resistance in some genetic profiles mainly originate in places with high concentration of animals, indicating that in intensive farming must be careful with the indiscriminate use of antibiotics. Keywords: pleurisy, P. multocida, pigs.